Day Care, Trade Unions, and the Women’s Movement: Trade Union Women Organize for Change - Leah, Ronnie (Making Knowledge Count: Advocacy and Social Science, 1991)
This case study of union women organizing for day care in Ontario analyses the emergence of a women's movement within labour. It provides a social history of women's organizing efforts in the Ontario labour movement, tracing political mobilization of support for universally accessible, publicly funded child care. In addition, day care sheds light on recent developments in two Canadian social movements: the labour movement and the women's movement. Developments in each of these areas have facilitated gains made by both. The active campaign of trade union women for women's equality in the unions has been integrally connected to the contemporary women's movement. While the growth of feminism established a foundation for the struggles of working-class women in unions around gender issues such as day care, a growing number of working women joined unions in the last decade to organize against the domination of the labour movement by men. --Introduction
Keywords: Action sociale; Sciences sociales Philosophie; Social action; Social sciences Philosophy